Síntese de ésteres fenilpropanóicos de álcoois monoterpênicos - Borges, Flávio Valadares Pereira (2014)
The phenylpropanoid esters of monoterpene alcohols are usually found in low concentrations in natural environments, which usually prevents some studies of toxicity and tolerance. Isolation from natural sources generally do not provide adequate quantities, mainly due to their occurrence at low concentrations. Substances such as: Bornyl Benzoate, Bornyl Salicylate, Bornyl p-coumarate, Bornyl Ferulate, Bornyl 3,4-methylenedioxy-trans-Cinnamate and trans-caffeate of α-Terpineol have presented several interesting pharmacological activities. This work aims to present alternatives for the preparation of these esters pathways such reactions Dartzen for preparation of acyl chlorides, esterification reactions of the type Shotten-Baumann reaction and the use of Wittig-Horner in getting the benzene esters of cinnamic some monoterpene alcohols such as (-)-borneol and α-terpineol. The identification of synthesized compounds was performed by analysis of 1H and 13C NMR and the data were compared with those in the literature for unambiguous assignment. The Shotten-Baumann reactions used to obtain the esters derived from (-)-borneol showed appropriate, to give yields between 84 and 40%. For the preparation of trans-caffeate of α-terpineol a Wittig-Horner reaction, with a yield of 20%, requiring further studies.